Total Quality Manufacturing (TQM) and Recommendations for Its Application in the Defense Industry: A Literature Review - Brata, Jun; Soediantono, Dwi (International Journal of Social and Management Studies, 2022)
The method of writing this article is a literature review, which is a review by collecting, understanding, analyzing and then concluding as many as 25 international journal articles published from 2010 to 2021 regarding the application of Total Quality Manufacturing (TQM) in various industrial sectors and the defense industry. The analysis used used 25 content analyzes of journal articles, which had been collected and then looked for similarities and differences and then discussed to draw conclusions. The results of the literature review analysis state that the application of Total Quality Manufacturing (TQM) contributes to expanding employee empowerment. Make employees more trained and have good skills. Employees feel more valued. For product consumers, of course Total Quality Management will provide benefits in the form of higher quality products received. Customers feel more cared for because their needs are met by the company. Maintain customer satisfaction. TQM makes companies focus on market demands, TQM inspires employees to provide the best quality in every activity, TQM channels the procedures that are important to obtain superior results,TQM helps to continuously test all processes to get rid of unnecessary and unproductive things, TQM supports companies to really understand the existing competition and to build an effective war strategy,TQM helps to establish good procedures for communication and reward good work. TQM helps to review what processes are needed to build a continuous development strategy. Total Quality Manufacturing (TQM) is recommended to be applied to the defense industry. Based on the literature review, Total Quality Manufacturing (TQM) is recommended to be applied to the defense industry.